HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU DENGAN PERILAKU PSN-DBD DI KELURAHAN SUNGAI JAWI PONTIANAK TAHUN 2013 - ., Uray Muttia Wulandari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background─Dengue hemorrhagic fever is an endemic disease inIndonesia. Prevention of dengue fever is needed to be done by the act ofPSN (mosquito nest erradication) which is done by mother. Behavior of PSNDHFis affected by various factors such as individual’s characteristic andknowledge.Objective─The aims are to know the characteristic, level of knowledge, andPSN-DHF behavior of mother to increase the success of DHF prevention.Method─Analitical cross sectional study. Data was gained from thequestionnaire filled by mothers who fit sampling criteria in Kelurahan SungaiJawi Pontianak in 2013.Result─There are 116 repondents taken as sample with characteristic themost are age 31-55 years old, middle level of education, do not work, haveincome amount more than province minimum wage,sufficient knowledge, andless behavior of PSN-DHF. Analysis data through Chi-square test resultedthat there are no association between mother’s age and amount of familyincome with behavior of PSN-DHF (p=0,186 and p=0,150), and there areassociation between level of education, occupational status, and knowledgewith behavior of PSN-DHF (p=0,033; p=0,021; and p=0,002).Conclusion─There is tendency for mothers who have high level ofeducation, occupation, and good knowledge to have good behavior of PSNDHF.Health information is needed for entire society to increase the behaviorof PSN-DHF.Keywords: mosquito nest eradication, characteristic, knowledge, behavior